10 cm2 nonfullerene solar cells with efficiency over 10% using HxMoO3-assisted growth of silver electrodes with a low threshold thickness of 4 nm. Issue 1 (4th December 2019) - Jiang, Xueshi; Sun, Lulu; Wang, Wen; Qin, Fei; Xie, Cong; Hu, Lin; Zhou, Yinhua
Abstract : 10 cm 2 nonfullerene solar cells show an efficiency up to 10.24% using silver electrodes grown on a chemically reactive H x MoO3 surface with a percolation threshold thickness as low as 4 nm for Ag films. Abstract : In this study, we report 10 cm 2 nonfullerene solar cells with power conversion efficiency of 10.24%. The demonstration of the large-area cells is based on the H x MoO3 -assisted growth of two silver electrodes, namely, the ultrathin-transparent electrode (on the top) and opaque electrode (at the bottom). The device structure has the configuration glass/H x MoO3 /opaque Ag (70 nm)/active layer/H x MoO3 /ultrathin Ag (8 nm)/MoO3 . The chemically reactive H x MoO3 could react with silver oxide during the growth of the initial few nanometers of silver, as inferred from X-ray spectroscopy measurements. The reaction increases the nucleus sites that assist the continuous and uniform growth of the silver films. The percolation threshold thickness of conductive ultrathin Ag films on H x MoO3 can be as low as 4 nm. The root-mean-square surface roughness of opaque silver (70 nm) grown on the H x MoO3 surface is as low as 1.06 nm. H x MoO3 facilitates the growth of uniform, continuous and smooth silver films that enable the efficient large-area nonfullerene organic solar cells.